Biomechanical and perceptual evaluation of the use of a servo-controlled power-assistance system in manual wheelchair mobility - Medola, Fausto O. [UNESP]; Bertolaccini, Guilherme S. [UNESP]; Silva, Sara R. M. [UNESP]; Lahr, Gustavo J. G.; Elui, Valeria M. C.; Fortulan, Carlos A. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This preliminary study investigated the effect of the implementation of a servo-controlled power assisted mechanism in a manual wheelchair on the demands of the upper limb muscles and the subjects' perception about the effort and difficulty to perform mobility tasks. The electromyographic activity of four upper limb muscles (pectoralis major, anterior deltoids, triceps and biceps) and the rate of perceived exertion and difficulty in six different wheelchair mobility tasks performed by eight subjects were analyzed comparatively with the use of two different wheelchairs: A standard manual device and a prototype of a servo-controlled power assisted wheelchair. The results show that the subjects considered easier and less strenuous to perform most of the wheelchair mobility tasks with the use of the power-assisted chair, in comparison to the manual wheelchair. Data from muscles' activity showed that moving on an ascent ramp with the servo-assisted wheelchair reduced the biomechanical demand on the upper limbs, in comparison with the standard wheelchair. However, the other five mobility tasks did not have the same results, suggesting that the servo-controlled mechanism still needs to be improved to provide consistent benefits for the users in terms of reducing the biomechanical loads during manual propulsion.
Keywords: Biomechanics; Mobility; Propulsion; Robotics; Wheelchairs